Analisis pengaruh motivasi dan disiplin kerja terhadap kinerja karyawan outsourcing: Analysis of the influence of work motivation and discipline on outsourcing employee performance - Indra Rahmat Arifin; Ageng Kanda Saepudin (Universitas Bojonegoro, 2024)
This research is quantitative in nature with a descriptive approach, aiming to evaluate the influence of motivation and work discipline on employee performance at PT. COPX Bandung. The method employed in this research is quantitative, collecting data from 50 members of the company's team as the sample. The analysis results prove that motivation and work discipline have a relevant or significant impact on employee performance. Employees with high motivation and work discipline tend to demonstrate good work practices. Recommendations for the company include identifying employees with high motivation and work discipline and providing support and potential development opportunities. This research contributes significantly to the progress of the company and provides valuable insights for further studies. Therefore, it can be concluded that having good motivation and work discipline will strengthen the values embraced by employees and create a positive work environment, which is key to improving employee performance